Realidade ou ficção? A influência da autopercepção como parceiro romântico e da autoestima na escolha e preferência de parceiros românticos - Mafra, Anthonieta Looman (2015)
In general, men and women look for characteristics that can indicate improvement of their reproductive success in their romantic partners. However, partner choice is not only based on what the individual want in a partner, but he/she also takes into consideration how they perceive themselves in a determined environment, in a way that self-perception can change according to the context where the individual is inserted in. Besides the environment, self-esteem can be a factor that modifies romantic partner preferences and the way that people choose these partners for being able to influence how people evaluate themselves. Most of the studies that originate today’s universal standards in the study of romantic partner were conducted with undergraduate students, which may limit the coverage of the conclusions for contemplating people of the same educational level and probably also socioeconomic status (SES). The present research, held in Brazil, where the social inequality rate is high, and part in Canada, country with low social inequality, had as goal verifying romantic partners preferences and choices and self-evaluation as romantic partners in different educational level and SES. Men, mainly of low SES, tend to prioritize social status when looking for a romantic partner while the universal pattern is the preference for physical attractiveness, and women of low SES seem to be aware of this preference when expressing that social status is important for their self-perception. In addition, the results corroborate the influence of the context, selfesteem, and SES in the self-perception as a romantic partner, though the latter two appear to modulate how the is the influence of the context on participants’ perception. Moreover, this research also indicated that the preferences appear to represent the choices for the most important characteristics for each sex, being the other characteristics probably modulated by the quantity of available participants in the environment.